Performance of micro and small foodpreneurs in Manipur during COVID-19 pandemic - SUBHRA SAIKAT ROY; ANANTA SARKAR; H NARESH SINGH; S K SHARMA; M A ANSARI; K H RISHIKANTA SINGH; G KADIRVEL; PUNITHA P; PINTUBALA KSHETRI; T H SURCHANDRA SINGH; K TAMREIHAO; CHONGTHAM RAJIV; et al. (The Indian Journal of Agricultural Sciences, 2022)
To critically assess the performance of micro and small foodpreneurs during COVID-19 pandemic in Manipur state of India, an online survey was conducted during the year 2020. The survey data was subjected to non-parametric statistical analysis using PROC NPAR1WAY and Dwass, Steel, Critchlow-Fligner multiple comparison analysis. The findings suggested that during COVID-19 pandemic, the micro and small foodpreneurs faced multifaceted challenges with respect to the number of employees, working hours, supply of raw material, selling mode, production, sale, turnover and the extent of loss, etc. The performance of different categories of foodpreneurs was compared based on the change in various performance indicators between pre-pandemic and pandemic period. The study also highlights the major problems faced by the foodpreneurs and remedial measures. This is the first report on the impact of COVID-19 pandemic on foodpreneurs from North East India.